PEMANFAATAN POTENSI LOKAL RUMPUT LAUT (EUCHEUMA COTTONII) DALAM PEMBUATAN STIK OLEH IBU-IBU PKK DI DESA BALAWELING 1 KECAMATAN SOLOR BARAT - Yosephina Margaretha J. Batafor; Maria Hermina Peransa Betan (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Seaweed is a marine plant belonging to the macroalgae group that lives attached to the seabed (benthic algae). As a natural resource commodity, seaweed has high economic value and great potential to be developed into various value-added processed products. However, in Balaweling 1 Village, West Solor District, cultivated Eucheuma cottonii seaweed is still sold as raw material at low prices. This condition indicates that local potential has not been optimally utilized to improve community welfare. This Community Service (PKM) activity aims to improve the understanding and skills of the community, especially the PKK (Family Welfare Movement) women's group, in processing seaweed into high-value snack sticks. The activity method uses a hands-on approach (learning by doing) that includes material preparation, seaweed stick processing, modern packaging using standing pouches, and digital marketing training through social media. The results of the activity showed an increase in the skills and creativity of participants in processing seaweed into attractive and durable processed products. The resulting seaweed stick products have a crunchy texture, savory taste, and modern packaging, thus having the potential to be marketed more widely. The conclusion of this activity was that seaweed processing training can increase economic independence and empower coastal women. Consequently, similar activities can serve as a model for sustainable, locally-based empowerment and encourage the formation of small community businesses based on local marine resources.